Recuperando la historia de los colombianos en Elizabeth: redefiniendo la historia de la ciudad - Avivi, Yamil (Sociedad y Economía, 2003)
This paper reports some of the results of a project of restitution of oral testimonies from Colombian migrants to Elizabeth (New Jersey, U. S. A.). A first objective intends to review some historical widespread versions that ignore the Latino presence in the city (which accounts for nearly half of today´s population) o that reduce it to the Cuban component (that numerically has been already surmounted by Colombians). A second objective tries to show, by means of collected stories, the way Colombians have lived the insertion to the local life ways since the sixties.